Riverside Remembered - Briggs, Wallace Neal, 1915- (Book collections on Project MUSE., 1992)
A moving personal memoir of Mississippi in the 1920s and the bitter harvest of racial repression. As the story opens, six-year-old Buster Briggs boards a Pullman car headed south over the Louisville and Nashville Railroad, and we embark with him on what will become his journey from childhood into adolescence. Bus Briggs is a white boy from Indiana who spends his summers and Christmases at his grandparents' Mississippi homeplace -- Riverside. Travel with him on this journey of discovery. Join Bus and his cousins as they string popcorn and chinaberries for the yule tree, savor ice cream made from.